Research trends of mesenchymal stem cells application in orthopedics: A bibliometric analysis of the past 2 decades - Deng, Zhibo; Luo, Fenqi; Lin, Yuan; Luo, Jun; Ke, Dianshan; Song, Chao; Xu, Jie (Frontiers in Public Health, 2022)
Background: Bibliometric analysis and visualization tools were used to determine the development trend of mesenchymal stem cells (MSCs) in orthopaedics in the past 20 years, so as to guide researchers to explore new directions and hotspots in the field in the future. Methods: In the Web of Science Core Collection, all articles about the application of MSCs in orthopaedics from 2002 to 2021 were searched. The qualitative and quantitative analysis was performed based on Web of Science and CiteSpace software. Results: A total of 2207 articles were retrieved. After excluding non-article articles such as review and letter and non-English language articles, 1489 articles were finally included. Over the past 2 decades, the number of publications on the application of MSCs in orthopaedic diseases increased. Among them, the United States, China, Japan and the United Kingdom have made significant contributions in this field. The most productive institution was Shanghai Jiao Tong University. Journal of Orthopaedic Research published the largest number of publications. The journal with the highest citation frequency was Experimental Hematology. The authors with the highest output and the highest citation frequency on average were Rochy S. Tuan and Scott A. Rodeo, respectively. "Mesenchymal stem cell", "In vitro" and "Differentiation" were the top three keywords that appeared. From the keyword analysis, the current research trend indicates that the primary research hotspots of MSCs in orthopaedics are the source of MSCs, in vitro experiments and the differentiation of MSCs into bone and cartilage. The frontiers of this field are the combination of MSCs and platelet‑rich plasma (PRP), the treatment of knee diseases such as osteoarthritis, osteogenic differentiation, and the application of biological scaffolds combined with MSCs. Conclusion: Over the past 2 decades, the application of MSCs in orthopaedic diseases has received increasing attention. Our bibliometric analysis results provide valuable information and research trends for researchers in the field to understand the basic knowledge of the field, identify current research hotspots, potential collaborators, and future research frontiers.